2022
DOI: 10.1186/s12974-022-02668-8
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection of mature neurons from immunocompetent mice generates a disease-associated microglia and a tauopathy-like phenotype in link with a delayed interferon beta response

Abstract: Background Zika virus (ZIKV) infection at postnatal or adult age can lead to neurological disorders associated with cognitive defects. Yet, how mature neurons respond to ZIKV remains substantially unexplored. Methods The impact of ZIKV infection on mature neurons and microglia was analyzed at the molecular and cellular levels, in vitro using immunocompetent primary cultured neurons and microglia, and in vivo in the brain of adult immunocompetent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In line with these findings, our study provides, to our knowledge, the first evidence for a role of Irf3 in the infection of murine cells by ZIKV. Moreover, we recently reported that primary cultured neurons (PCNs) show a delayed activation of the Ifnb1 expression upon ZIKV exposure compared with MEFs, and that this delay is even longer in PCNs derived from CC071 compared with CC001 [ 34 ]. The identification of the Irf3 mutation in CC071 provides an explanation for this observation, although it would require confirmation in B6- Irf3 KO PCNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, our study provides, to our knowledge, the first evidence for a role of Irf3 in the infection of murine cells by ZIKV. Moreover, we recently reported that primary cultured neurons (PCNs) show a delayed activation of the Ifnb1 expression upon ZIKV exposure compared with MEFs, and that this delay is even longer in PCNs derived from CC071 compared with CC001 [ 34 ]. The identification of the Irf3 mutation in CC071 provides an explanation for this observation, although it would require confirmation in B6- Irf3 KO PCNs.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between the consequences of Irf3 deficiency in in vitro and in vivo experiments likely reflect differences between a single cell type model with an intrinsic capacity to mount a more or less IRF3-dependent IFN-I response, and a multicellular organism in which the paracrine effect of IFN-I produced by the most reactive cells induces protection of other, less reactive, cell types. In fact, we have recently reported such cooperation between neurons and microglia cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have consistently demonstrated that ZIKV can infect the neurons, resulting in cell death and impaired neurodevelopment, ultimately leading to the development of microcephaly ( Alpuche-Lazcano et al., 2021 ; Hughes et al., 2016 ; Lin et al., 2017 ; Oh et al., 2017 ). In addition to neural cells, studies have shown that glial cells, including microglia and astrocytes, are also significant targets of ZIKV infection in the brain ( Jorgačevski et al., 2019 ; Manet et al., 2022 ; van den Pol et al., 2017 ). Astrocytes are the most abundant glial cells in the central nervous system and play crucial roles in the immune response, synaptic guidance, and maintenance of the integrity of the blood-brain barrier (BBB) ( Ransom and Ransom, 2012 ).…”
Section: Introductionmentioning
confidence: 99%